2023
DOI: 10.1111/tid.14150
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of one and two booster doses of SARS‐CoV‐2 mRNA vaccines in kidney transplant recipients: A randomized clinical trial

Petr Drenko,
Martin Kacer,
Lukas Kielberger
et al.

Abstract: BackgroundKidney transplant recipients are at risk for a severe course of COVID‐19 with a high mortality rate. A considerable number of patients remains without a satisfactory serological response after the baseline and adjuvant SARS‐CoV‐2 vaccination schedule.MethodsIn this prospective, randomized study, we evaluated the efficacy and safety of one and two booster doses of mRNA vaccines (either mRNA‐1273 or BNT162b2) in 125 COVID‐19 naive, adult kidney transplant recipients who showed an insufficient humoral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Indeed, recent data suggest that monoclonal antibody prophylactic therapy elicits a strong humoral response against SARS-CoV-2 in SOT-Rs [ 48 , 49 , 50 ]. Finally, the use of mRNA booster vaccines has been shown to elicit a stronger and broader immune response to SARS-CoV-2 Omicron variants compared to the wild-type monovalent booster vaccines [ 51 , 52 ]. Therefore, we conclude that the ongoing longitudinal evaluation of SARS-CoV-2 humoral and cellular responses to mRNA-based vaccine in SOT-Rs might be valuable and necessary to allow the frequent re-evaluation of an ever-changing viral landscape in immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent data suggest that monoclonal antibody prophylactic therapy elicits a strong humoral response against SARS-CoV-2 in SOT-Rs [ 48 , 49 , 50 ]. Finally, the use of mRNA booster vaccines has been shown to elicit a stronger and broader immune response to SARS-CoV-2 Omicron variants compared to the wild-type monovalent booster vaccines [ 51 , 52 ]. Therefore, we conclude that the ongoing longitudinal evaluation of SARS-CoV-2 humoral and cellular responses to mRNA-based vaccine in SOT-Rs might be valuable and necessary to allow the frequent re-evaluation of an ever-changing viral landscape in immunocompromised individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Drenko et al showed the formation of human leukocyte antigen antibodies in 11% of patients after the second booster dose. 5 However, the vast majority of these antibodies were not donorspecific and there were no changes in creatinine upon follow-up. Thus, the theoretical risk of rejection needs to be balanced by the risk of severe coronavirus disease 2019 (COVID-19) infection and its downstream effects of pneumonitis, acute kidney injury, and the potential for death in kidney transplant recipients where advanced age and multiple comorbidities may also increase risk of complications.…”
mentioning
confidence: 96%
“…In this issue of Transplant Infectious Diseases, Drenko et al performed a randomized trial of one and two booster doses of SARS-CoV-2 monovalent mRNA vaccines in kidney transplant recipients. 5 The study participants had received two doses as their primary series almost 7 months prior and had not formed an antibody response. They had also not previously been infected with SARS-CoV-2.…”
mentioning
confidence: 99%
See 1 more Smart Citation